Characteristics of Groundwater on the Eastern Slope of Mount Ciremai, Kuningan Regency, West Java, Indonesia - Dianardi, Kholqi; Jumhari, Jumhari; Hadian, M. Sapari Dwi; Waliyana, Teuku Yan (UIR PRESS, 2018)
Water is a very important component for the survival of living things. Groundwater is water that has better quality compared to other water types, so groundwater is widely used to meet the needs of clean water. The research area is located on the eastern slope of Mount Ciremai which is a volcanic area that has great groundwater potential, it is seen from the many springs with large groundwater discharge. The study aims to determine the physical and chemical characteristics of groundwater on the eastern slopes of Mount Ciremai which also the district of Kuningan. The research method is done by collecting geological data and hydrogeological data. To find characteristics of groundwater chemistry, groundwater sampling was taken at 10 locations, and then tested the laboratory to determine the chemical content of groundwater. Based on the results of the research, the physical characteristics of water were shown with EC values ranging from 76,8 to 228 µS/Cm, TDS from 50 to 151 mg/L, pH value from 6.4 to 7.65, water temperature 19.3 to 25.9 oC. While one of the observation location is HC. 11 is a hot springs that has a water temperature of 36.1 oC , EC 832 µS/Cm, TDS 428 mg/L and pH 6.8. Chemical analysis results from pipe diagram show the developing facies are Ca:HCO3, Ca.Mg:HCO3, Na.K:Cl.